THE IMPACT OF ADEQUACY, LOSS, AND RECREATION IN THE TRANSLATION OF THE IMAGE OF QUEENS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The international development of literature, the translation of works into various languages, and their dissemination to a global readership today represent not only an important stage of cultural and social progress but also hold vital significance for the formation of international relations and intercultural communication. The translation process itself is highly complex and requires a multi-layered intellectual and cultural dialogue. In this process, the translator’s skill in preserving the meaning, spirit, and aesthetic form of the original text, accurately conveying it across evolving cultures, and delivering it effectively to the audience is of utmost importance.